IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBENTUKAN SIKAP SOSIAL KEBANGSAAN PESERTA DIDIK MELALUI PEMBELAJARAN IPS (STUDI LITERATUR) - Sari, Reni Novita; Resmi, Ayu Citra (IJTIMAIYA: Journal of Social Science and Teaching, 2020)
Character education is needed to form atitude, personality and morals of a nation. In its application character education can be applied through the learning process one of which is in learning ocial science. The study aims to determine the role of social science in the formation of learners character and to know the application or implementation of character education in social science. This reseach method uses literatur, literatur research metodhs theough various agreed procedures. The results of this study are educators or teachers and schools play an important role in shaping the character of students through schools rules, activitiesthat are followed and learning process. Character education is applied to students through social science tailored to the material and conditions of students. Leraning methods and teacher understanding of the material also affect the development of character education. In learning social science also has the same goal as character education which is to create good citizens and have moral values.